Liturgiczne obrzędy jubileuszu małżeństwa - Kulbacki, Piotr (Studia Pastoralne, 2026)
The paper presents the development of liturgical rites related to the Wedding Anniversary. It reveals the process of evolution of marriage rituals: from domestic rituals to wedding ceremonies celebrated in churches. Post-Tridentine Roman Ritual (1614) as well as its complements introduced at the beginning of the 20th century (1913 and 1925) did not include jubilee celebrations. Wedding anniversary celebrations were finally added to the Roman Ritual in 1952. Pius V’s Roman Missal did not include rites of anniversaries. Only the Missal of John XXIII on the occasion of the 25th and the 50th wedding anniversary indicated votive Mass formulas: De Sanctissima Trinitate, De Beata Maria Virgine including the additional oration from Pro gratiarum actione. The celebration was to be concluded with the prayer over the spouses, included in the Roman Ritual. The first edition of the post-conciliar Ordo celebrandi matrimonium (1969) did not contain any reference to the anniversary. Editio typica altera (1991) provided the appropriate formulas of the Mass and blessings based on De bendictionibus (1984). Polish editions of the Sacrament of Marriage rites preserve the traditions of the hymn Veni Creator and the binding of hands with the stole during the rite of marriage and – similarly – the rite of the anniversary. Further editions of the Missal of Paul VI provide forms of the Mass for the anniversary placing them among ritual masses (1970, 1975) or votive masses (2002). Liturgical books currently provide celebration patterns for the 25th, 50th and 60th wedding anniversary. They also encourage priests, deacons and lay persons to give blessings on other occasions. The renewal of wedding vows ceremony as an element of the mystagogy of the Sacrament of Marriage is widely practiced in Domestic Church oasis retreats of the Light-Life Movement.